Integration of BIM technologies into the strategy of business process optimization of a construction enterprise - RIZUN, Dmytro (Ways to Improve Construction Efficiency, 2025)
The integration of BIM technologies (Building Information Modeling) into the strategy of business process optimization of a construction enterprise shapes a new management model oriented toward data, transparency, and analytical interaction. BIM serves as the central element of digital transformation, ensuring the comprehensive integration of architectural, engineering, financial, and logistical processes within a unified information-analytical environment. This approach creates prerequisites for synchronization among all structural units of the enterprise, reduces managerial errors, and increases the efficiency of decision-making. A key effect of BIM implementation is the formation of an end-to-end digital cycle in which information is continuously updated and used for planning, control, and forecasting. BIM technologies enable integration with ERP, CRM, and SCM systems, creating an analytical “core” of management that unites the technical, economic, and organizational levels of enterprise activity. Digital models allow multidimensional analysis of processes in 4D–6D formats, taking into account temporal, financial, and operational parameters. The efficiency of BIM depends on the maturity level of its implementation – from the isolated use of 3D models to fully developed digital twins that reflect the real state of an object in real time. Such an environment strengthens the potential of predictive analytics, creates conditions for risk management, cost optimization, and quality control throughout all stages of a construction project’s life cycle. Integrating BIM technologies transforms management processes from reactive to proactive, where data analytics becomes the foundation for strategic decision-making. The digital interaction between humans, technology, and information forms a new management culture in which cognitive flexibility, systems thinking, and analytical transparency play key roles. BIM evolves beyond a design tool into an intelligent platform for sustainable development, efficient resource utilization, and increased competitiveness of construction enterprises.